2012
DOI: 10.1371/journal.pone.0047221
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Attentional Disengagement from Stimuli Matching the Contents of Working Memory in Social Anxiety

Abstract: Although many cognitive models in anxiety propose that an impaired top-down control enhances the processing of task-irrelevant stimuli, few studies have paid attention to task-irrelevant stimuli under a cognitive load task. In the present study, we investigated the effects of the working memory load on attention to task-irrelevant stimuli in trait social anxiety. The results showed that as trait social anxiety increased, participants were unable to disengage from task-irrelevant stimuli identical to the memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 76 publications
(108 reference statements)
1
7
0
Order By: Relevance
“…Our results are consistent with previous studies showing reduced attentional control in the context of non-threat distractors in socially anxious individuals (Moriya & Tanno, 2008; Moriya & Sugiura, 2012; Morrison & Heimberg, 2013). However, the current findings raise the possibility that previous findings were driven by the high degree of overlap between social anxiety and depression.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are consistent with previous studies showing reduced attentional control in the context of non-threat distractors in socially anxious individuals (Moriya & Tanno, 2008; Moriya & Sugiura, 2012; Morrison & Heimberg, 2013). However, the current findings raise the possibility that previous findings were driven by the high degree of overlap between social anxiety and depression.…”
Section: Discussionsupporting
confidence: 93%
“…In two studies, self-reported attentional control was negatively correlated with social anxiety, even after statistically controlling for the effects of depression (Moriya & Tanno, 2008; Morrison & Heimberg, 2013). In a third study, social anxiety was positively correlated with difficulty disengaging attention from non-emotional, task-irrelevant stimuli being held in working memory (Moriya & Sugiura, 2012). However, this effect was not moderated by working memory load.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to working memory, research suggests that social anxiety may be associated with difficulty filtering nonemotional task-irrelevant information from visual working memory (Moriya & Sugiura, 2012a), particularly for those with low working memory capacity (Moriya & Sugiura, 2013) and regardless of whether cognitive load is low or high (Moriya & Sugiura, 2012b). A few studies have examined biases for socially threatening stimuli in social anxiety.…”
mentioning
confidence: 99%
“…This may comprise a functional mechanism whereby, under conditions of strong 5‐HT 4 ‐receptor activation pattern separation is promoted (in CA1 and DG) at the expense of pattern completion in CA3. This in turn could explain why under circumstances where 5‐HT homeostasis is impaired (Heisler et al, ; Kusserow et al, ; Pennanen et al, ), inadequate 5‐HT 4 ‐receptor activation leads to redundant or excessive encoding of details of a given experience (Moriya and Sugiura, ).…”
Section: Discussionmentioning
confidence: 99%